Stability of milk fatty acid profile during simulated shipping for analysis by gas chromatography - A.J. Schmidt; R. Bomberger; K.J. Harvatine (JDS Communications, 2021)
Milk fat trans-10 C18:1 can be used in diagnosing low milk fat production on dairy farms because it is a specific marker of biohydrogenation-induced milk fat depression. Individual fatty acids (FA), including the trans C18:1 isomer, can be determined only by gas-liquid chromatography. The analysis is currently available at a limited number of laboratories and often requires long-distance shipping. Expedited shipping with dry ice or ice packs is expensive. Therefore, the objective of this study was to determine the effect of heat treatment before shipping, shipping temperature, and shipping time on milk FA profile. Samples were collected from 3 farms on 2 occasions and stored in a polystyrene foam cooler with an ice pack, at room temperature, or at 37°C for 1, 2, 3, and 7 d. Heating the sample before shipping, shipping temperature, and shipping time had very little effect on any FA analyzed. Differences observed were of small magnitude and not of practical importance, demonstrating that milk FA profile is expected to be very stable during shipping. Based on this, we propose that freezing samples and shipping in a sealed bag by second-day shipment is appropriate and demonstrated that this had little effect on FA profile of 48 milk samples. Importantly, these methods are recommended only for gas-liquid chromatography analysis of FA profile. Freezing is not appropriate for shipping for analysis by mid-infrared spectrometry-based methods or methods quantifying compounds per unit of milk because it is difficult to homogenize samples after freezing or extended shipping that results in denaturization of proteins and breaking of fat globules.